VISITOR SATISFACTION ATTENDING FESTIVAL IN BALI: CASE OF SANUR VILLAGE FESTIVAL 2018 - I Gusti Ayu Dewi Hendriyani (Institut Pariwisata dan Bisnis Internasional, 2019)
Festivals or special events have been one of the fastest developing tourism attractions in many countries. Bali as tourism destination have many activities on tourism event such as festivals or special events to attract more tourists to come every year. Sanur Village Festival (SVF) declared by the government as one of the top ten national tourism event in Indonesia. SVF is an annual event since 2006. Its community event founded by Sanur Development Foundation (YPS) which is a combination of several large-scale activities involving food festival, creative economy exhibition, various contests and competitions, art and cultural attractions, music as well as various types of environmentally-friendly activities. Quality of activities and service on an event is dynamic conditions that relate to fullfill the visitors expectation. In tourism event, quality of activities and service becomes success parameter as indication of satisfaction. The aim of these research is to know the visitors satisfaction attending festival in Bali, case study of SVF 2018. Sample of the research is visitors of SVF 2018 during period 22-26 August 2018 with total 135 respondents. The method of this research is quantitative method with analysis factor confirmatory using SPSS. Using teory from Crompton (2003) there are six factors and twenty six variables that were observed. The factors and variables are convenience value (F1) through five variables, service value (F2) through six variabels, perceived price (F3) through four variables, aesthetic value (F4) through four variables, playful value (F5) through four variables and social value (F5) through three variables. Finding in this research about visitors satisfaction attending festival in Bali, case of SVF 2018 is in good condition according to the guest overall comments. The leading factor and variable are playfull value (F5) and X21 (enjoyable). The strategic implication that should be done by management of SVF or Sanur Development Foundation to the result of reserach is to maintain what has been good and improve which one is unfavourable by make evaluation and standarization of work for all vendors/ suppliers that supported the festival.Festivals or special events have been one of the fastest developing tourism attractions in many countries. Bali as tourism destination have many activities on tourism event such as festivals or special events to attract more tourists to come every year. Sanur Village Festival (SVF) declared by the government as one of the top ten national tourism event in Indonesia. SVF is an annual event since 2006. Its community event founded by Sanur Development Foundation (YPS) which is a combination of several large-scale activities involving food festival, creative economy exhibition, various contests and competitions, art and cultural attractions, music as well as various types of environmentally-friendly activities. Quality of activities and service on an event is dynamic conditions that relate to fullfill the visitors expectation. In tourism event, quality of activities and service becomes success parameter as indication of satisfaction. The aim of these research is to know the visitors satisfaction attending festival in Bali, case study of SVF 2018. Sample of the research is visitors of SVF 2018 during period 22-26 August 2018 with total 135 respondents. The method of this research is quantitative method with analysis factor confirmatory using SPSS. Using teory from Crompton (2003) there are six factors and twenty six variables that were observed. The factors and variables are convenience value (F1) through five variables, service value (F2) through six variabels, perceived price (F3) through four variables, aesthetic value (F4) through four variables, playful value (F5) through four variables and social value (F5) through three variables. Finding in this research about visitors satisfaction attending festival in Bali, case of SVF 2018 is in good condition according to the guest overall comments. The leading factor and variable are playfull value (F5) and X21 (enjoyable). The strategic implication that should be done by management of SVF or Sanur Development Foundation to the result of reserach is to maintain what has been good and improve which one is unfavourable by make evaluation and standarization of work for all vendors/ suppliers that supported the festival.